2020
DOI: 10.21203/rs.2.21534/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nursing and midwifery students’ experiences and perception of their clinical learning environment in Malawi: A mixed method study

Abstract: BackgroundThe clinical learning environment is an important part of the nursing and midwifery training as it helps students to integrate theory into clinical practice. However, not all clinical learning environments foster positive learning. The aim of this study was to assess the experiences and perception of nursing and midwifery students of their clinical learning environment in Malawi.Methods A mixed-methods approach was used to collect data from nursing and midwifery students. Data were collected using a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The satisfaction of both parties is important for the continuation of this practice. The study by Mbakaya et al (2020) articulates the students' dissatisfaction as 'lack of resources', 'poor relationship with staff' and 'disliking the clinical posting'.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The satisfaction of both parties is important for the continuation of this practice. The study by Mbakaya et al (2020) articulates the students' dissatisfaction as 'lack of resources', 'poor relationship with staff' and 'disliking the clinical posting'.…”
Section: Objectivesmentioning
confidence: 99%
“…The satisfaction of both parties is important for the continuation of this practice. The study by Mbakaya et al (2020) articulates the students' dissatisfaction as 'lack of resources', 'poor relationship with staff' and 'disliking the clinical posting'.The staff nurses did comment on the work overload as a complicating aspect of supervision.Lack of 'continuous medical education' to update skill for supervising students, 'nurse-clientThe author is Asst.…”
mentioning
confidence: 99%
“…The preceptors in the present study are employees of the clinical facilities hence this could influence how positive they perceived the clinical placement area. Other studies have indicated the need to improve the clinical placement area (Kananu et al, 2020;Mbakaya et al, 2020;Rajeswaran, 2017). It can therefore be suggested that the clinical placement area should be assessed at the beginning of every academic year to ensure that students get optimal clinical placement experiences.…”
Section: Clinical Placement Areamentioning
confidence: 99%
“…Job satisfaction can be achieved through immediate feedback and mentoring because learning new strategies that were not taught in books can increase staff productivity. Mentoring the new generation of nurses is supported by the three subthemes of learning from a mentor's experiences, accepting the criticism of your senior nurse, and bridging the theory into practice (Mbakaya et al 2020).…”
Section: Discrimination From the Communitymentioning
confidence: 99%